AB0830 Role of anti-IFI16 antibodies and NT-PROBNP as candidate biomarkers in systemic sclerosis. (23rd January 2014) - Meroni, P.L.; Chighizola, C.; Schioppo, T.; Artusi, C.; Caneparo, V.; Gariglio, M.; Gualtierotti, R.; Lubatti, C.; Ingegnoli, F.; Zeni, S.; Borghi, M.
Abstract : Background: Systemic sclerosis (SSc) is an autoimmune condition characterized by polymorphic clinical presentations, high morbidity and mortality. It would be therefore valuable to identify biomarkers for diagnosis, prediction of organ involvement and disease subset. Objectives: Aim of this study was to retrospectively assess the role of serum anti-IFI16 antibodies and NT-proBNP levels as candidate biomarkers in a cohort of scleroderma patients. Methods: 100 SSc patients (49 with diffuse disease) were enrolled in this study; patients with PAH and renal insufficiency were excluded from NT-proBNP analysis. We investigated the relationship between the two candidate biomarkers and several scleroderma clinical manifestations (severe interstitial lung disease, cardiac involvement, digital ulcers, calcinosis, arthritis) and variables (age, disease duration, BP, Hb, mRSS, ESR, DLCO). Serum anti-IFI16 antibodies were detected by a home-made semi-quantitative ELISA, NT-proBNP levels were measured by the Roche immunoassay. Statistical analysis was performed using STATA 11. Results: NT-proBNP was significantly increased in patients with heart involvement compared to those without (p=0.0003, 95%CI 57-232). A cut-off value of 130pg/mL gave a specificity of 70% and a sensibility of 74% to predict cardiac involvement (area under ROC curve 0.746; 95%CI 0.63-0.86), with a predictive negative value of 85%. Moreover, NT-proBNP levels>130pg/mL were strong predictors of heart involvement (OR 7). Not surprisingly, NT-proBNP levels were negatively correlated with LVEF (r=-0.266; p=0.002). Conversely, there was no association between anti-IFI16 antibodies and cardiac involvement (p=0.505). No other association was reported between the two candidate biomarkers and clinical manifestations of SSc. There was no significant difference between disease subsets in NT-proBNP levels (p=0.12) and anti-IFI16 antibodies titers (p=0.71). We report a significant association between NT-proBNP and age (r=0.315; p=0.003), disease duration (r=0.287; p=0.008), ESR (p=0.0086) and DLCO (r=-0.356; p=0.001) while anti-IFI16 antibodies were not significantly associated with any of the clinical variables. Conclusions: Given the high negative predictive value, NT-proBNP may be a useful tool to identify scleroderma heart disease. SSc related cardiac involvement still heralds a poor prognosis, with 1% of annual mortality attributable to cardiac disease. Future studies are warranted to establish its role as surrogate biomarker. Disclosure of Interest: None Declared